1997
DOI: 10.1023/a:1026461825570
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis induced by sodium butyrate treatment increases immunogenicity of a rat colon tumor cell line

Abstract: We have recently demonstrated that a treatment combining the cell differentiating agent sodium butyrate (NaBut) and interleukin-2 (IL2) resulted in a remission of established peritoneal colorectal carcinomatosis in rats. NaBut or IL2 treatment alone, never cured these tumour-bearing rats. In the present investigation, we report that NaBut-treatments induce apoptosis in the colonic cancer cells both in vitro and in vivo. We postulated that the significant therapeutic effect of NaBut/IL2 treatment can be mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…In fact, although butyrate arrests normal cells in G 1 , it induces apoptosis in transformed cells within 4 hours after G 1 -S arrest. 58,[65][66][67][68][69][70][71][72][73][74][75][76][77] Thus, the activities of butyrate that cause cell cycle arrest may be problematic when the drug is used in patients with hemoglobinopathies unless it is given intermittently, which, in turn, limits the amount of ␥-globin and the proportions of F cells that can be induced.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, although butyrate arrests normal cells in G 1 , it induces apoptosis in transformed cells within 4 hours after G 1 -S arrest. 58,[65][66][67][68][69][70][71][72][73][74][75][76][77] Thus, the activities of butyrate that cause cell cycle arrest may be problematic when the drug is used in patients with hemoglobinopathies unless it is given intermittently, which, in turn, limits the amount of ␥-globin and the proportions of F cells that can be induced.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptotic bodies were prepared and purified as previously described [6]. Briefly, PROb were treated for 3 days with sodium butyrate (5 mM).…”
Section: Generation Of Apoptotic Cellsmentioning
confidence: 99%
“…In order to evaluate the implication of apoptotic bodies in curative treatments of tumor-bearing rats, we developed a therapy which included injections of apoptotic bodies from tumor cells [6]. Briefly, 10 days after intraperitoneal injection of cancer cells, treatment with apoptotic bodies and IL2 was performed ( fig.…”
Section: Curative Treatments Of Tumor-bearing Rats With Apoptotic Bodiesmentioning
confidence: 99%
“…It was shown that DC pulsed with apoptotic tumor cells induce a strong Ag-specific T cell response in vitro, and when injected into mice, such pulsed DC induced tumor-specific cytotoxic T cell responses and long-term protection from parental tumor challenge (24) (in these models, DC activation might result from the in vitro manipulation of the DC). It was also suggested that an increase of the apoptotic process in poorly immunogenic tumor cells can lead to a remission of established peritoneal carcinomatosis (25), and more recently, that apoptotic but not necrotic tumor cells are efficient vaccines in vivo (26). Using the RMA T cell lymphoma model, it was demonstrated that the injection of apoptotic tumor cells results in the priming of a functional long-lasting tumor-specific immune response, and that this occurs via cross-priming (27).…”
mentioning
confidence: 99%